(untitled) (Malaysian Management Journal, 2000)
This paper is focusing on the use of Importance-Performance (IP) Analysis to measure the destination’s perforÂmance in offering tourism products. IP method is often used in research due to its simplicity, ease of use and usefulness in aiding decision-making processes. IP is also promising since it examines both expectations i.e. the importance of each attribute, and the performance of the attributes in fulfilling the expectation. Thus it aids tourism providers in determining what attributes are most important to tourists so that the attractiveness of the attributes can be improved. Using the data from the researcher’s study on positioning in Kedah, a further analysis was carried out to determine Kedah’s attractiveness in the eyes of its international market. Results of the IP analysis showed distinct difference in perception among clusters. For practical use of information generÂated by the analysis, it was suggested that information on the two biggest clusters i.e. Cluster 2 and Cluster 3 be used to improve Kedah’s tourism. The information revealed that according to Cluster 2, Kedah has to improve on attributes such as comfort at place of accommodation, friendliness of local people, services in. restaurants at place of accommodation, clean beaches, services in restaurants outside places of accommodation, standard of catering at restaurants outside places of accommodation, tourist information centre/booth, shopping facilities, local traffic, standard of catering at places of accommodation, isolated beaches, entertainment facilities, accesÂsibility/transport and night life. For Cluster 3, we need to concentrate on improving attributes including beauÂtiful scenery, comfort at place of accommodation, clean beaches, value for money, climate and weather; lack of crowdedness, services in restaurants at places of accommodation, standard of catering outside places of acÂcommodation, services in restaurants outside places of accommodation, shopping facilities, tourists informaÂtion centre, accessibility/transport and local traffic. The research recommended the need for Kedah’s tourism planners and providers to pay attention to these attributes in planning and providing tourism offerings.